Relationship between nostalgia marketing and traditional Sonoran desserts - Sánchez Caro, Daniela Karina (Posgrados de la División de Ciencias Económica Administrativas, 2022)
At the beginning of the 1990s, various investigations developed the concept of 'nostalgia' to define consumer behaviors and preferences related to emotions and memories (Toledo and Lopes, 2016). Nostalgia marketing develops strategies based on people's emotions. In the specific case of food, it is especially relevant when it is linked to traditional products that are part of the customs of a town or community, where specific forms of preparation and preparation are maintained. consumption (Camarena and Sanjuán, 2008). In the spirit of delving into the relationship between nostalgia marketing and Sonoran traditional foods, in this research a diagnosis was made on the state of the art of nostalgia marketing applied to traditional foods, particularly in the case of desserts. traditional Sonorans. For this, a documentary investigation is carried out, where the information on the traditional desserts of Sonora, their commercialization and studies of the marketing of nostalgia towards this type of products are strengthened.